Studi Komparasi Akad Ijarah dan Jua'alah Serta Aplikasi Keduanya Dalam Ekonomi Modern - Al-Faizin, Abdul Wahid; Muhyidin, Muhyidin; Hafid, Abdul (ITB AAS INDONESIA Surakarta, 2024)
Islam is present and believed by its adherents as a teaching that regulates all forms of human activity universally and comprehensively, between humans as creatures with Allah as their Creator and between humans as fellow creatures of His creation. So as a logical consequence of this, the fiqh used as a guideline or foundation is divided into two, namely fiqh of worship and fiqh of mu'amalah. One form of activity in daily life related to fiqh mu'amalah is ijarah (rent) and Ju'alah (reward). So the purpose of this study will examine in more depth the ijarah and ju'alah contracts in Islamic economics with the fiqh muamalah approach. It is hoped that the results of this study can be used as a reference for readers to better understand the ijarah and ju'alah contracts in the future.